Evaluasi Penggunaan Antibiotik Profilaksis Cefazolin Pada Pasien Operasi di Rumah Sakit Premier Bintaro - Humaira Fadhilah; Nurul Chasanah; Ridwan Ruswendi (Edu Masda Journal, 2019)
Prophylactic antibiotics are antibiotic used by patients who have not been infected but are thought to have the chance to get an infection or if an infection will have an adverse effect on the patient. The use of prophylactic antibiotics is needed because it is proven to prevent or reduce the incidence of infection. Inaccurate selection of antibiotic, indication, dosage, time of administration, duration of administration, and route of administration causes inappropriate treatment infections with antibiotic. The objective of this study was to evaluate the use of prophylactic antibiotics cefazolin in surgical patients at the premier bintaro hospital in the period of july – December 2017. This study is non experimental with retrospective data collection and analyzed with quantitative descriptive. This research was carried out at premier bintaro hospital from april until may. Samples were taken by purposive sampling method. Samples are medical record of surgery patients who use cefazolin as prophylactic antibiotic, with 231 samples. Data collection instrument uses a checklist of accuracy of the use prophylactic antibiotic filled by researcher. The result showed the highest presentation of the age patients was adult age (18-40 ) year is 45,9%, right indication of the use 100%, right dosis 99,1%, right time administration 77,5%, right duration administration 93,5%, and right route administration 100 %. The conclusion of this study is stil inaccuracies in the administration of prophylactic antibiotic cefazolin in surgical patients in term of dosage, time of administration, and duration of administration.